2022
DOI: 10.1109/access.2022.3224127
|View full text |Cite
|
Sign up to set email alerts
|

PID Control Design Using AGPSO Technique and Its Application in TITO Reverse Osmosis Desalination Plant

Abstract: Desalination plants have an important concern regarding controlling the permeate flow rate and pH during operability. This paper proposes the proportional integral derivative (PID) control design using modified Particle Swarm Optimization (PSO) techniques called autonomous groups PSO (AGPSO) in the two-input two-output (TITO) RO desalination plant to control the permeate flow rate and pH. Here, three different versions (AGPSO1, AGPSO2, and AGPSO3) of the AGPSO algorithm are utilized to design PID control for t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 25 publications
(8 citation statements)
references
References 40 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Numerous authors have addressed the segmentation of nuclei using various conventional approaches, including mathematical morphology, pixel classification, level sets, and graphbased segmentation methods [19,20,24,36], due to its crucial role in the automatic interpretation of stained tissue sections. While nucleus identification is often carried out by a spatially restricted convolutional neural network (SC-CNN), a new adjacent ensemble predictor (NEP) that is paired with CNN has been suggested to more reliably predict the class label of cell nuclei [25].…”
Section: Nuclei Segmentationmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous authors have addressed the segmentation of nuclei using various conventional approaches, including mathematical morphology, pixel classification, level sets, and graphbased segmentation methods [19,20,24,36], due to its crucial role in the automatic interpretation of stained tissue sections. While nucleus identification is often carried out by a spatially restricted convolutional neural network (SC-CNN), a new adjacent ensemble predictor (NEP) that is paired with CNN has been suggested to more reliably predict the class label of cell nuclei [25].…”
Section: Nuclei Segmentationmentioning
confidence: 99%
“…The nuclei are crucial in and of themselves for assessing and verifying the presence of illness and the speed at which it spreads. A few of the feature detection techniques that have been employed successfully and efficiently are discussed in this study [33][34][35][36][37][38][39][40][41][42][43].…”
Section: Detection Of Featuresmentioning
confidence: 99%
“…Similarly, Ju et al 44 suggested a hybrid strategy of WOA based on nonlinear convergence factor, chaos initialization, and mutation concepts. Further, Chakraborty et al proposed various artificial intelligence models using WOA and their variants for numerous applications, such as for COVID-19 X-ray image segmentation 45 , global optimization 46 , 47 , numerical optimization 48 , and other applications 49 52 .…”
Section: Introductionmentioning
confidence: 99%
“…PID parameter optimization (or sometimes referred as parameter tuning) is key for effective performance of userdefined control tasks in manipulators [7], magnetic levitation [8], industrial plants [9], higher order systems [10], and other industrial settings. Nonetheless, tuning the parameters of PID control systems is challenging due to expensive evaluations of real-world surrogates and the requirement for fast adaptation to new tasks [6], [11].…”
Section: Introductionmentioning
confidence: 99%